Perbandingan Ibu Yang Memberikan ASI Eksklusif Dengan Non Eksklusif Pada Masa Pandemi Covid-19: Literature Review - Ruthmita Septiani; Yulia Irvani Dewi; Wasisto Utomo (Yayasan Jompa Research and Development, 2022)
Introduction: COVID-19 is of particular concern to all countries, one of which is Indonesia, because it has an impact on all sources, including maternal and child health services. During a pandemic, mothers are advised to continue giving breast milk to their children because it contains the perfect blend of antibodies, vitamins and immune factors needed to increase the baby's immune system, children's growth and development, and to save on family spending costs. This literature study aims to look at comparisons between mothers who give exclusive and non-exclusive breastfeeding during the COVID-19 pandemic. Method: The method used is literature review. Search for articles based on 3 databases, namely Google scholar, science direct and pubmed for mothers who breastfeed during the COVID-19 pandemic. The keywords in English are exclusive breastfeeding AND non-exclusive breastfeeding AND COVID-19 pandemic, as well as in Indonesian, namely exclusive AND non-exclusive breastfeeding AND the COVID-19 pandemic. Results: The results of the literature review show that of the 5 articles the majority of respondents are aged 20-35 years (26.54%). Of the 807 respondents, 595 (73.73%) mothers gave exclusive breastfeeding and 212 (28.27%) mothers gave non-exclusively. Conclusion: It can be concluded from the 5 articles that mothers who give exclusive breastfeeding are higher than non-exclusive where there is a significant difference between mothers who give exclusive and non-exclusive breastfeeding. Keywords: exclusive breastfeeding; non-exclusive; covid-19 pandemic.